Application Of Running Text On A 16x32 Dot Matrix Based On Arduino Uno Using Bluetooth - Wildan Al-faridzi, Mochamad; Seliwati (Nusa Putra University, 2024)
This study aims to develop a running text application using a 16x32 dot matrixmodule controlled by an Arduino Uno and connected via Bluetooth. Thesystem is designed to display moving text messages that can be easily changedthrough a mobile device. The methodology includes designing andprogramming the Arduino to control the dot matrix and implementing the HC05 Bluetooth module for wireless communication. The results indicate thatthe system can display various messages with adjustable speed and direction,as well as a quick response to commands sent via a smartphone app. Testingdemonstrates the system's reliability in various environmental conditions.This running text implementation is expected to be useful in variousapplications, such as public information, advertising, and othercommunication media. The study also contributes to the development ofinteractive systems based on microcontrollers with Bluetooth connectivity.